2019
DOI: 10.1093/mnras/stz2820
|View full text |Cite
|
Sign up to set email alerts
|

H α morphologies of star clusters: a LEGUS study of H ii region evolution time-scales and stochasticity in low-mass clusters

Abstract: The morphology of HII regions around young star clusters provides insight into the timescales and physical processes that clear a cluster's natal gas. We study ∼700 young clusters (≤10Myr) in three nearby spiral galaxies (NGC 7793, NGC 4395, and NGC 1313) using Hubble Space Telescope (HST ) imaging from LEGUS (Legacy Extra-Galactic Ultraviolet Survey). Clusters are classified by their Hα morphology (concentrated, partially exposed, no-emission) and whether they have neighboring clusters (which could affect t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 37 publications
7
85
0
Order By: Relevance
“…If cloud disruption occurs soon after the onset of star formation within a cloud, then the resulting efficiency of the conversion of gas into stars will be low. This idea is supported by recent observations showing that young stellar clusters and H II regions with ages in the range 1-10 Myr have already dispersed their parent cloud (Kawamura et al 2009;Whitmore et al 2014;Hollyhead et al 2015;Corbelli et al 2017;Grasha et al 2019;Hannon et al 2019;Kruijssen et al 2019b;Chevance et al 2020). The various feedback mechanisms that may be responsible for the rapid dispersal of the natal cloud are discussed in Sect.…”
Section: Fast and Inefficient Star Formationsupporting
confidence: 64%
See 1 more Smart Citation
“…If cloud disruption occurs soon after the onset of star formation within a cloud, then the resulting efficiency of the conversion of gas into stars will be low. This idea is supported by recent observations showing that young stellar clusters and H II regions with ages in the range 1-10 Myr have already dispersed their parent cloud (Kawamura et al 2009;Whitmore et al 2014;Hollyhead et al 2015;Corbelli et al 2017;Grasha et al 2019;Hannon et al 2019;Kruijssen et al 2019b;Chevance et al 2020). The various feedback mechanisms that may be responsible for the rapid dispersal of the natal cloud are discussed in Sect.…”
Section: Fast and Inefficient Star Formationsupporting
confidence: 64%
“…the ages of young stellar clusters and their association to nearby GMCs to estimate how quickly the feedback from the young stellar population drives GMC dispersal. For instance, Hollyhead et al (2015) and Hannon et al (2019) found that clusters in four nearby galaxies are no longer embedded once they reach ages of ∼ 4-5 Myr. For clusters in M51, Grasha et al (2019) find a GMC dispersal timescale of ∼ 6 Myr, consistent with the measurement for the same galaxy by Chevance et al (2020), who find 4.8 +2.1 −1.1 Myr.…”
Section: Feedback Timescalesmentioning
confidence: 99%
“…Alvensleben 2003;Groves et al 2008;Boquien et al 2010;Reines et al 2010;Pellegrini et al 2020). PHANGS-HST observations, however, benefit from the combination of HST's angular resolution and relative proximity of PHANGS galaxies, such that star clusters and surrounding H II regions can often be spatially disentangled, except for (1) crowded regions where it is still often unclear which star clusters are responsible for ionizing a given patch of H α emission and (2) clusters with compact H α morphologies (Hannon et al 2019). The YGGDRASIL tracks with zero covering fraction (i.e.…”
Section: Single-aged Stellar Population Models and Nebular Emissionmentioning
confidence: 99%
“…The stellar population will also be fainter than a higher mass population which fully populates the IMF. This effect is called sampling stochasticity and it results in a broad range of possible luminosities and colours for these low-mass clusters (Barbaro & Bertelli 1977;Girardi & Bica 1993;Lançon & Mouhcine 2000;Bruzual 2002;Cerviño & Luridiana 2006;Deveikis et al 2008;Fouesneau et al 2012;Hannon et al 2019). In colour-colour space, clusters, which may be stochastically sampling the IMF, can be found in the region bluer in V−I than the SSP tracks at 1-5 Myr.…”
Section: Stochasticity In Sampling the Imfmentioning
confidence: 99%
See 1 more Smart Citation